The Formation of the Goldfish-Like Fish Derived From Hybridization of Female Koi Carp × Male Blunt Snout Bream - Wang, Yude; Yang, Conghui; Luo, Kaikun; Zhang, Minghe; Qin, Qinbo; Huo, Yangyang; Song, Jia; Tao, Min; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2018)
Goldfish (Carassius auratus var., GF; 2n=100) is the most popular ornamental fish in the world. It is assumed that GF evolved from red crucian carp (Carassius auratus red var., RCC; 2n=100). However, this hypothesis lacks direct evidence. Furthermore, our knowledge of the hybridization’s role in forming new species is sparse. In this study, the goldfish-like fish with twin-tail (GF-L; 2n = 100) is produced by self- crossing of red crucian carp-like fish (RCC-L; 2n = 100) derived from the distant crossing of koi carp (Cyprinus carpio haematopterus, KOC; 2n = 100;♀) with blunt snout bream (Megalobrama amblycephala, BSB; 2n = 48;♂). The phenotypes and genotypes of GF-L and RCC-L are very similar to those of GF and RCC, respectively. Microsatellite DNA and 5S rDNA analyses revealed that GF-L and RCC-L are closely related to GF and RCC, respectively. The presence of the twin-tail of GF-L is related to a base mutation in chordinA from G in RCC-L to T in GF-L, indicating that the lineage including RCC-L and GF-L is good at studying gene variation and function. By mapping the sequences of 5S rDNA in GF-L and RCC-L to the genome of each of CC and BSB, the average similarity of each of GF-L and RCC-L to CC is obviously higher than each to BSB, supporting that the genome of each of RCC-L and GF-L is mainly inherited from CC. GF-L and RCC-L are proved to be homodiploids mainly derived from the genome of CC with some DNA fragments from BSB. The reproductive traits of GF-L and RCC-L are quite different from those of their parents, but are the same as those of GF and RCC. RCC-L easily diversified into GF-L, suggesting that RCC and GF evolved within the same period in their evolutionary pathway. This study provides direct evidence for koi carp-color crucian carp-goldfish evolutionary pathway triggered by distant hybridization, which has important significance in evolutionary biology and genetic breeding.